1999
DOI: 10.1016/s0014-5793(99)01326-5
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing, expression and biochemical characterization of the Porphyromonas gingivalis pepO gene encoding a protein homologous to human endothelin‐converting enzyme

Abstract: We have determined the nucleotide sequence of the clone pAL2 obtained from Porphyromonas gingivalis 381 in the previous study [Ansai et al. (1995) Microbiology 141, 20472 052]. The DNA sequence analysis of this fragment revealed one complete ORF and one incomplete ORF. The ORF encoded a protein (PgPepO) of 690 amino acids with a calculated molecular weight of 78 796. The deduced amino acid sequence exhibited a significant homology with human endothelin-converting enzyme (ECE)-1. Recombinant PgPepO was purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 35 publications
0
36
0
1
Order By: Relevance
“…FTT1209c encodes a predicted M13 metallopeptidase with striking similarity to mammalian endothelin-converting enzyme (ECE-1). FTT1209c has several homologs, including PepO from Porphyromonas gingivalis, which plays a role in host cell invasion (1,4). FTT1209c has been annotated as a pseudogene in the sequenced F. tularensis strain SchuS4 (35).…”
Section: Discussionmentioning
confidence: 99%
“…FTT1209c encodes a predicted M13 metallopeptidase with striking similarity to mammalian endothelin-converting enzyme (ECE-1). FTT1209c has several homologs, including PepO from Porphyromonas gingivalis, which plays a role in host cell invasion (1,4). FTT1209c has been annotated as a pseudogene in the sequenced F. tularensis strain SchuS4 (35).…”
Section: Discussionmentioning
confidence: 99%
“…As determined by a BLAST search of the National Center for Biotechnology Information nonredundant protein sequence database and database of unfinished genomes (1, 2) only a few gram-negative organisms sequenced to date, such as Porphyromonas gingivalis, Shewanella putrefaciens, Caulobacter crescentus, Haemophilus ducreyi, and Legionella pneumoniae, possess regions of DNA with homology to the M13 metallopeptidases. Of these organisms only P. gingivalis has been shown experimentally to produce an enzyme with catalytic activity similar to the mammalian enzymes of this category (4). The majority of bacteria that have sequence homology to the mammalian M13 metallopeptidases are gram-positive and have an intimate association with mammals.…”
Section: Resultsmentioning
confidence: 99%
“…S. parasanguis rPepO was shown here by inhibition studies to be more similar to ECE-1 than to NEP, since it was more sensitive to phosphoramidon than it was to thiorphan. It has been suggested for the same reason that P. gingivalis PepO may also be more akin to ECE-1 than to NEP (4).…”
Section: Resultsmentioning
confidence: 99%
“…In P. gingivalis, the protease showed activity against Big Endothelin (33), but the results were controversial, and ET-1 generation could not be confirmed by enzyme-linked immunosorbent assay (ELISA). Here, we found that the mycobacterial enzyme Zmp1 does not act as an ECE that converts Big ET-1 into ET-1 mature peptide (Fig.…”
Section: Discussionmentioning
confidence: 99%